2010
DOI: 10.3389/fncir.2010.00120
|View full text |Cite
|
Sign up to set email alerts
|

Differential Axonal Projection of Mitral and Tufted Cells in the Mouse Main Olfactory System

Abstract: In the past decade, much has been elucidated regarding the functional organization of the axonal connection of olfactory sensory neurons to olfactory bulb (OB) glomeruli. However, the manner in which projection neurons of the OB process odorant input and send this information to higher brain centers remains unclear. Here, we report long-range, large-scale tracing of the axonal projection patterns of OB neurons using two-photon microscopy. Tracer injection into a single glomerulus demonstrated widely distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
124
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(143 citation statements)
references
References 46 publications
10
124
0
1
Order By: Relevance
“…The relatively recent advent of approaches to visualize glomeruli in vivo combined with genetico-viral based tracing techniques, have made it feasible to address this question. The results of these studies have largely confirmed those implications from older tracing studies revealing, for example, that projections from sister MTCs of a single glomerulus, and those of a single cell, disperse to innervate multiple POC structures in a manner that is independent of the spatial location of an individual glomerulus (Nagayama et al, 2010;Ghosh et al, 2011;Miyamichi et al, 2011;Sosulski et al, 2011). Course topography is evident in some MOB targets as noted earlier for the AON (Miyamichi et al, 2011).…”
Section: Inputs From Mobsupporting
confidence: 74%
See 2 more Smart Citations
“…The relatively recent advent of approaches to visualize glomeruli in vivo combined with genetico-viral based tracing techniques, have made it feasible to address this question. The results of these studies have largely confirmed those implications from older tracing studies revealing, for example, that projections from sister MTCs of a single glomerulus, and those of a single cell, disperse to innervate multiple POC structures in a manner that is independent of the spatial location of an individual glomerulus (Nagayama et al, 2010;Ghosh et al, 2011;Miyamichi et al, 2011;Sosulski et al, 2011). Course topography is evident in some MOB targets as noted earlier for the AON (Miyamichi et al, 2011).…”
Section: Inputs From Mobsupporting
confidence: 74%
“…The caudal parts of piriform, periamygdaloid and lateral entorhinal cortices by contrast receive terminals primarily or exclusively from MCs. A recent study (Nagayama et al, 2010) confirmed older findings that TCs, compared to MCs, tend to project more strongly to rostral POC areas (e.g., olfactory tubercle, AON). Other results did not detect differences in the projections of deep or internal TCs compared to their sister MC cohorts (Ghosh et al, 2011).…”
Section: Inputs From Mobsupporting
confidence: 51%
See 1 more Smart Citation
“…Strotmann (&) Institute of Physiology, University of Hohenheim, Garbenstrasse 30, 70593 Stuttgart, Germany e-mail: strotman@uni-hohenheim.de glomeruli are currently unknown. By means of various labeling studies of the last decades, the general targets of projection neurons (mitral/tufted cells) from the main olfactory bulb (MOB) have been identiWed throughout the olfactory cortex, including the anterior olfactory nucleus, the piriform cortex and the entorhinal cortex (Haberly and Price 1977;Scott et al 1980;Luskin and Price 1982;Carlsen et al 1982;Ojima et al 1984;Buonviso et al 1991;Nagayama et al 2010;Miyamichi et al 2011;Ghosh et al 2011) as well as the cortical amygdala (Kevetter and Winans 1981b;Licht and Meredith 1987). In this context, it is interesting to note that in a recent study, Baum and coworkers have shown that an application of tracer in the ventral domain of the MOB resulted not only in the labeling of the typical target sites, but labeled Wbers were unexpectedly also found in the anterior and posterior subdivisions of the medial amygdala (Kang et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The odour map in the OB is transmitted by output neurons, mitral cells, to higher olfactory centres and eventually translated to elicit appropriate behavioural and physiological responses. Recent anatomical studies in mice showed that axons from identified glomeruli project diffusely throughout the piriform cortex [6][7][8][9] , the largest target area of the OB, and that piriform neurons receive convergent inputs from multiple mitral cells distributed throughout the OB 10 . These findings are consistent with an optical imaging study that found no apparent spatial organization of odour-evoked activity patterns in the piriform cortex 11 .…”
mentioning
confidence: 99%